PEMETAAN PERKEMBANGAN BISNIS DIGITAL ISLAM DI INDONESIA: ANALISIS BIBLIOMETRIK - Jessika Gafur Lamba; Sudirman; Ridwan Kambau; Syaifullah (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2026)
Abstract This study explores the development of Islamic Digital Business in Indonesia, focusing on the growth and trends of digital transformation within Islamic business practices from 2011 to 2026. With the rapid growth of digital technologies, this research examines how Islamic principles are integrated into digital business models, particularly in the context of e-commerce, small and medium-sized enterprises (SMEs), and digital innovation. The study aims to identify key themes, emerging trends, and gaps in the existing literature, providing a comprehensive understanding of the field. A bibliometric analysis of relevant scholarly articles is conducted to assess global contributions and identify leading countries, institutions, and authors. The research methodology includes thematic analysis to explore dominant themes such as business performance, digital transformation, and business sustainability, along with underexplored areas like halal certification and Islamic finance. The study also examines the social and ethical implications of digital business in the Islamic context, emphasizing the importance of aligning business practices with Islamic values. Findings reveal that while e-commerce and digital transformation dominate the research landscape, areas like Islamic finance and sustainability remain underexplored. The research highlights the importance of interdisciplinary collaboration and suggests future research directions, particularly in integrating AI with Islamic business models and ensuring ethical and sustainable business practices. This study significantly contributes to the understanding of Islamic digital business in Indonesia, offering insights that can guide future research and practices in the field. Keyword: Islamic Digital Business, Islamic E-commerce, Digital Transformation